Pollutant load estimation and load reduction target (LRT) projection for total maximum daily load (TMD) allocation on tropical rivers - Bello, Nura; Jamil, Nor Rohaizah; Looi, Ley Juen; Ng, Keng Yap (Elsevier, 2024)
Pollutant load may be defined as the mass of a substance that passes a particular point of a river in a specified amount of time. Meanwhile, estimation of pollutant loading and identification of their sources is crucial to environmental management and planning. For the first time (in this study), Flow rate measurement was used to estimate daily pollutant loading from Intermittent water quality concentration data, using a 2-dymensional Water Quality Analyser (WQA). Subsequently, Total Maximum Daily Load (TMDL) was determined using the Load duration approach, while Load Reduction Targets were projected for the future, the using regression option of trend analysis available in the WQA. Out of the ten parameters used for the study, BOD, NH3, and TSS have been identified as the most critical pollutants in the area, which require average load reduction of 3898.88 kg-day, 1053.28 kg-day, and 444,716.50 kg-day respectively, to achieve water quality class II, until 2030. Moreover, the study reveals that the load reduction target for BOD and TSS would decrease in the future, while that of NH3 increases (p < 0.001). This is even as significant variability also exists for the projected load reduction target over the months throughout the projected period (p < 0.01). It was concluded that WQA provides a cost and time effective, and a reliable means for estimation of Pollutant load and projection of Load Reduction Target. The study recommends source identification for the critical pollutants into the river and allocation of TMDLs using the dynamic flow approach.